Improvised Field Expedient Method for Renal Replacement Therapy in a Porcine Model of Acute Kidney Injury. (2nd December 2021) - Hoareau, Guillaume L.; Beyer, Carl A.; Kashtan, Harris W.; Walker, Lauren E.; Wilson, Christopher; Wishy, Andrew; Grayson, J. Kevin; Stewart, Ian J.
ABSTRACT: Objective: Dialysis patients may not have access to conventional renal replacement therapy (RRT) following disasters. We hypothesized that improvised renal replacement therapy (ImpRRT) would be comparable to continuous renal replacement therapy (CRRT) in a porcine acute kidney injury model. Methods: Following bilateral nephrectomies and 2 hours of caudal aortic occlusion, 12 pigs were randomized to 4 hours of ImpRRT or CRRT. In the ImpRRT group, blood was circulated through a dialysis filter using a rapid infuser to collect the ultrafiltrate. Improvised replacement fluid, made with stock solutions, was infused pre-pump. In the CRRT group, commercial replacement fluid was used. During RRT, animals received isotonic crystalloids and norepinephrine. Results: There were no differences in serum creatinine, calcium, magnesium, or phosphorus concentrations. While there was a difference between groups in serum potassium concentration over time ( P < 0.001), significance was lost in pairwise comparison at specific time points. Replacement fluids or ultrafiltrate flows did not differ between groups. There were no differences in lactate concentration, isotonic crystalloid requirement, or norepinephrine doses. No difference was found in electrolyte concentrations between the commercial and improvised replacement solutions. Conclusion: The ImpRRT system achieved similar performance to CRRT and may represent a potential option for temporary RRT following disasters.